Diversity instead of competition and displacement : diversification of in-company vocational education as a strategy for securing the skilled workforce - Bahl, Anke [Verfasser]; Dietzen, Agnes [Verfasser]; Dorsch-Schweizer, Marlies [Verfasser] (My University, 2011)
"This article examines the options open to companies for meeting qualifications needs, with particular attention to company-based initial and continuing vocational education and training (IVET/ CVET). It presents selected results from a survey of experts which shed light on present assumptions about the trend for companies to recruit more academically qualified employees and erosion of the significance of occupational training in the workplace. The findings show that companies are increasingly relying on internal recruitment strategies and developing initiatives to combine company-based competence development with academic learning. Far from exhibiting a general bias towards academic qualifications, companies are seeking to recruit staff from diverse educational backgrounds." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.3.2 Anforderungen & Bedarfe; S 5.3 Personalentwicklung; G 2.4.1 Bildungs- und Berufswege; S 3.2 Unternehmen und Behörden; Qualifikationsbedarf; Qualifikationsanforderung; Personalgewinnung; Berufsnachwuchs; Beruflicher Aufstieg; Unternehmen